PENERAPAN METODE PISANG BATITA UNTUK MENINGKATKAN KEMAMPUAN MELENGKAPI CERITA RUMPANG - Utama, Muhammad Reva; Gusrayani, Diah; Djuanda, Dadan (Jurnal Pena Ilmiah, 2017)
In the preliminary data at fourth grade in SDN Cisalak IV, students were having problems in completing incomplete story. It was because they used the learning methods that do not involve students in learning. Therefore, applied a methods of Pisang Batita to improve writing skills for incomplete story and aims to improve the planning and the implementation of the teachers performance, Â students activity, and outcome of students learning. Research used is classroom action research model by Kemmis and Taggart. The research results with using Pisang Batita methods have increasing for every cycle. In teachers performance in cycle III increased come to 100%. For students activity in cycle I 36,83%, cycle II 78,95%, and cycle III 95,24%. And for a completed learning outcome in cycle I 52,63%, cycle II 78,95%, and cycle III 90,48%. It can be concluding that Pisang Batita methods for the real application can increasing outcome of students learning in complete incompleting story.Â Â